(untitled) (Proceedings International Conference on Fisheries and Aquaculture, 2022)
Coral trout (Plectropomus leopardus) is one of the grouper species with high economic value. The demand for fingerlings has been considerably increased in recent years. Dependence on the wild broodstock should be reduced gradually and replaced with domesticated from hatchery production. Institute for Mariculture Research and Fishes Extension (IMRAFE) has succeeded in coral trout culture and selected domesticated broodstock using a fast-growth marker and now has a third-generation (F3) of coral trout. Observation of gonad development and initial spawning of third-generation (F3) coral trout was carried out. The study aimed to understand gonadal development and initial spawning of coral trout F3 as an alternative for wild broodstock used in grouper hatchery activities. The study used 100 fishes of 31 months old coral trout F3 and observed for 11 months from January – November 2017. The research includes analysis of coral trout F3 gonad development, cultured and initial spawned of coral trout F3. The result shown in the population of coral trout F3 was male, transition, and female. Stage of female gonad maturation was III, IV, and V. The fecundity range 175.478 - 1.777.988 eggs, and coral trout F3 was spawned with quality still low. Increasing spawning quality can be done by improving feed management and hormonal stimulation.